Detection of the vaginal microflora in Pregnant and nonpregnant women using culture-independent method - Adnan H. Aubaid1 , Samira R. Gahadeer2 , Noor M. Jabar2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Bacterial Vaginosis (BV)is a disorder characterized by alterations of the vaginal flora with acquisition of diverse communities of anaerobic and facultative bacteria and depletion of the usually dominant lactobacilli. Objective: To conduct and characterize the main bacterial players in BV affected pregnant and non- pregnant women. Method: The BV work included collecting vaginal swabs from 158 women (18-45) years old.The samples were subjected in a laboratory to Amsel’s clinical criteria (ACC) and Nugent score system (NSS). The clinical diagnosis of BV was comprehensive when at least three ACCs were present out of a total four criteria (pH of vaginal secretions(Vss),Vaginal discharge ,Clue cells and Wiff (sniff) test). Results: The findings of the ACC and NSS revealed BV in 32 pregnant women(Pw) and 55 non pregnant women(Npw). In details, the ACC identified 39 (15 Pw and 24 Npw) positive samples. On the other hand, NSS unveiled that 48 (17 Pw and 31 Npw)with Vss were positive to BV. The bacterial isolates were distributed over the age categories (18-47 years old) of the Pw and Npw, in all age categories, (18-23, 24-29, 30-35, 36-41, and 42-47) year old, respectively. Conclusion:The presented work, here, provides beneficial data obtained by using feasible techniques with high degrees of reliability to overcome setbacks generated from the use of cultivation techniques.